High yielding mungbean variety ‘NIFA Mung-25’: A newly developed high-yielding mungbean [Vigna radiata (L.) Wilczek] variety with improved resistance to major diseases - Khattak, Gul Sanat Shah; Saeed, Iqbal; Ahmad, Shahzad; Ullah, Ghulam (International Journal of Applied and Experimental Biology, 2026)
An exotic mungbean genotype ‘V2802’ acquired from the World Vegetable Center (WVC) was hybridized with the Mungbean Yellow Mosaic Virus (MYMV) tolerant variety ‘Ramzan’ in spring 2012 at the Nuclear Institute for Food & Agriculture (NIFA), Peshawar, Pakistan. The F1 generation was raised in spring 2013, whereas F2-F6 populations were planted during the Kharif (Summer to Monsoon) seasons 2013-2017. Single plants/progenies’ selections were based on specific criteria, i.e., green seed color, better plant type, higher grain yield, and MYMV tolerance. A best-performing progeny, NFM-103-30 (NIFA Mung-25), was selected and evaluated in replicated yield trials at NIFA, various locations in Khyber Pakhtunkhwa (KP), and in the National Uniform Yield Trials (NUYTs) across Pakistan during 2018–2023. At NIFA and other locations of the Khyber Pakhtunkhwa (KP) province, NFM-103-30 (NIFA Mung-25) outperformed the check varieties, producing the highest average yield of 2,062 kg ha-1 compared to the check varieties Ramzan (1,768 kg ha-1), AZRI Mung-18 (1,698 kg ha-1), and NIFA Mung-19 (1,757 kg ha-1), with an average yield increase of 23.2%. In NUYTs conducted in 2022, NFM-103-30 (NIFA Mung-25) produced the highest mean yield of 1,323 kg ha-1 against the national check variety AZRI Mung Jumbo (1,267 kg ha-1) across KP. Similarly, during evaluation in NUYT-2023, NFM-103-30 (NIFA Mung-25) produced a grain yield of 1,207 kg ha-1, out-yielding the check variety NIAB Mung-2021 (1,010 kg ha-1). The candidate genotype/line also showed resistance to MYMV under field conditions. Based on its excellent performance in terms of grain yield across KP, the KP Seed Council approved NIFA Mung-25 as a new commercial mungbean variety for general cultivation in KP on August 6, 2025.